The Effect of Video Learning Media on Communication Skills and Creativity of Students of The History Study Program of Stkip Yayasan Abdi Pendidikan - Nahdatul Hazmi; Nurhizrah Gistituati; Mega Iswari (MultiTech Publisher, 2025)
This study aims to examine the influence of the use of video media on communication skills and creativity of students of the STKIP History Study Program, Yayasan Abdi Pendidikan Foundation. Video media was chosen because it is considered to facilitate more interactive and effective learning. This study uses an experimental method with a pretest-posttest design. The respondents of this study were 50 students who were divided into two groups: an experimental group that used video media in learning and a control group that used traditional methods. Data was collected through observations, questionnaires, and tests of communication and creativity skills. The results showed a significant increase in communication skills and creativity of students who used video media compared to the control group. This study concludes that video media has a positive influence on improving students' communication skills and creativity.